Dog behavior co-varies with height, bodyweight and skull shape. - Paul D McGreevy (Public Library of Science (PLoS), 2013)
Dogs offer unique opportunities to study correlations between morphology and behavior because skull shapes and body shape are so diverse among breeds. Several studies have shown relationships between canine cephalic index (CI: the ratio of skull width to skull length) and neural architecture. Data on the CI of adult, show-quality dogs (six males and six females) were sourced in Australia along with existing data on the breeds' height, bodyweight and related to data on 36 behavioral traits of companion dogs (n = 8,301) of various common breeds (n = 49) collected internationally using the Canine Behavioral Assessment and Research Questionnaire (C-BARQ). Stepwise backward elimination regressions revealed that, across the breeds, 33 behavioral traits all but one of which are undesirable in companion animals correlated with either height alone (n = 14), bodyweight alone (n = 5), CI alone (n = 3), bodyweight-and-skull shape combined (n = 2), height-and-skull shape combined (n = 3) or height-and-bodyweight combined (n = 6). For example, breed average height showed strongly significant inverse relationships (p<0.001) with mounting persons or objects, touch sensitivity, urination when left alone, dog-directed fear, separation-related problems, non-social fear, defecation when left alone, owner-directed aggression, begging for food, urine marking and attachment/attention-seeking, while bodyweight showed strongly significant inverse relationships (p<0.001) with excitability and being reported as hyperactive. Apart from trainability, all regression coefficients with height were negative indicating that, across the breeds, behavior becomes more problematic as height decreases. Allogrooming increased strongly (p<0.001) with CI and inversely with height. CI alone showed a strong significant positive relationship with self-grooming (p<0.001) but a negative relationship with chasing (p = 0.020). The current study demonstrates how aspects of CI (and therefore brain shape), bodyweight and height co-vary with behavior. The biological basis for, and significance of, these associations remain to be determined.